Teachers’ Attitudes toward Attention-Deficit or Hyperactivity Disorder in Primary Schools of Kirkuk, Iraq: A Cross-Sectional Study - Redha, Salih Ali; Ahmad, Bestoon M (Central Asian Journal of Medical and Natural Science, 2025)
Among school-age children, Attention Deficit Hyperactivity Disorder (ADHD) is one of the most prevalent neurodevelopmental diseases. Attention Deficit Hyperactivity Disorder (ADHD) has a substantial influence on academic and social outcomes, with teachers playing an important role in early detection and intervention. Despite its global prevalence (5-11%), teachers’ attitudes, which are crucial for inclusive education, have received little attention in Iraq. This descriptive cross-sectional study was conducted among 419 primary school teachers across Kirkuk City, Iraq, from November 2024 to May 2025. Using random sampling, participants were recruited from 88 schools (36 public, 47 special public, and 5 private special education institutions). Data were collected through a validated 22-item questionnaire assessing, Sociodemographic, and Attitudes toward ADHD (3-point Likert scale, Cronbach’s α=0.81) Statistical analysis in IBM SPSS v 20 included, Descriptive statistics and independent t-tests, ANOVA, Pearson’s r). Most teachers (97.9%) held neutral attitudes, with only 2.1% expressing strong positive/negative views. Male teachers reported significantly more positive attitudes than females (mean difference = 1.45, p < 0.001). Class size weakly correlated with attitudes (r = 0.132, p = 0.007), while age, religion, and education level showed no significant associations (p > 0.05). While ADHD awareness is prevalent, attitudes remain largely neutral, influenced more by gender and classroom context than sociodemographic. Findings underscore the need for mandatory ADHD training programs to fill the gap between proactive aid and awareness.